A Comprehensive Survey of Deep Learning Models Based on Keras Framework - Chicho, Bahzad Taha; Bibo Sallow, Amira (Journal of Soft Computing and Data Mining, 2021)
Python is one of the most widely adopted programming languages, having replaced a number of those in the field. Python is popular with developers for a variety of reasons, one of which is because it has an incredibly diverse collection of libraries in which users can run. This paper provides the most current survey on Keras, which is a Python-based deep learning Application Programming Interface (API) that runs on top of the machine learning framework TensorFlow. The mentions library is used in conjunction with TensorFlow, PyTorch, CODEEPNEATM, and Pygame to allow integration of deep learning models such as cardiovascular disease diagnostics, graph neural networks, identify health issues, COVID-19 recognition, skin tumors, image detection, and so on, in the applied area. Furthermore, the author used Keras details, goals, challenges, and significant outcomes, as well as the findings, obtained using this method. Keywords: